2018
DOI: 10.1002/bdd.2123
|View full text |Cite
|
Sign up to set email alerts
|

An iminium ion metabolite hampers the production of the pharmacologically active metabolite of a multikinase inhibitor KW‐2449 in primates: irreversible inhibition of aldehyde oxidase and covalent binding with endogenous proteins

Abstract: We previously reported that KW-2449, (E)-1-{4-[2-(1H-Indazol-3-yl)vinyl]benzoyl}piperazine, a novel multikinase inhibitor developed for the treatment of leukemia patients, was oxidized to an iminium ion intermediate by monoamine oxidase B (MAO-B) and then converted to its oxo-piperazine form (M1) by aldehyde oxidase (AO). However, it was found that the significant decrease in the pharmacologically active metabolite M1 following repeated administration of KW-2449 in primates might hamper the effectiveness of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The piperazine ring of KW-2449, a multikinase inhibitor developed for treatment of leukemia, was oxidized to iminium ion by MAO-B and then by AO to the pharmacodynamically active piperazinone metabolite (Figure A) . The iminium ion intermediate of KW-2449 was also an irreversible inhibitor of AO, possibly through covalent binding to the enzyme . A similar metabolic pathway was observed for 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP), a dopaminergic pro-neurotoxin which induces parkinsonism in humans and other primates (Figure B). , The morpholine ring of momelotinib, an inhibitor of Janus kinase 1/2 and activin A receptor type 1, was first oxidized by CYPs to iminium ion and then by AO to the corresponding morpholin-3-one metabolite (Figure C) .…”
Section: Substrate Specificity and Reactions Catalyzedmentioning
confidence: 80%
“…The piperazine ring of KW-2449, a multikinase inhibitor developed for treatment of leukemia, was oxidized to iminium ion by MAO-B and then by AO to the pharmacodynamically active piperazinone metabolite (Figure A) . The iminium ion intermediate of KW-2449 was also an irreversible inhibitor of AO, possibly through covalent binding to the enzyme . A similar metabolic pathway was observed for 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP), a dopaminergic pro-neurotoxin which induces parkinsonism in humans and other primates (Figure B). , The morpholine ring of momelotinib, an inhibitor of Janus kinase 1/2 and activin A receptor type 1, was first oxidized by CYPs to iminium ion and then by AO to the corresponding morpholin-3-one metabolite (Figure C) .…”
Section: Substrate Specificity and Reactions Catalyzedmentioning
confidence: 80%
“…KW-2449 is a multikinase inhibitor that was previously under investigation for the treatment of leukemia. The drug, which has been discontinued from further development, displayed unexpected rapid metabolism to an oxo-piperazine metabolite in clinical trials (Hosogi et al 2018 ). The pharmacologically active metabolite was determined to be generated via sequential metabolism by MAO B to an iminium ion intermediate, followed by AOX-mediated oxidation to the oxo-piperazine metabolite (Table 15 , Fig.…”
Section: Examples Of Substrates and Reactions Resulting In The Format...mentioning
confidence: 99%
“…33,76 A mechanism for the time-dependent inhibition (TDI) of CYP1A2 by proprietary compound DSP-1053 and the irreversible inhibition of AO by proprietary compound KW-2449 have both been attributed to iminium ion intermediates. 66,77,78 Rimonabant has been reported to be metabolized by CYP3A4 to form a highly cytotoxic reactive iminium ion metabolite that covalently binds to cellular proteins. 48,49 Recently, Tang et al reported the iminium ion intermediates formed from pemigatinib caused mechanism-based inactivation of P450 CYP3A.…”
Section: ■ Discussionmentioning
confidence: 99%